Pupuk Organik Cair Dari Limbah Padat Penyulingan Sereh - Mudarakna, Fathara; Salam, Abdul Haris (Politeknik Negeri Lhokseumawe, 2022)
Fertilizer is one of the components needed by plants to get additional nutrients so that they can grow well and are not susceptible to disease. There are various types of plant fertilizers on the market and most of them are chemical fertilizers with inorganic synthetic content. The content is thought to be not good for health when applied to food plants in excess. Meanwhile, organic fertilizers are safer for humans because they consist of organic ingridients. Liquid organic fertilizer can be interpreted as a fertilizer that is formed naturally through a fermentation process that results in decay. In this study, the sample used was citronella waste as the main raw material obtained from the distillery. The fermentation method used is anaerobic. Based on the results of fermentetion carried out for 23 days, the pH of organic fertilizers was found to be in the range 4-5.39 where the range was still in accordance with the standard range of 4-8. The temperature is at room temperature with an averege of 30.8˚C. The levels of macronutrients produced have not yet reached the standard. Based on the results of the study, it can be concluded that the use of citronella waste alone cannot achieve the required levels of macro nutirents. Additional fermentation time as well as other components are suggested to get different results